Clinical value of enzyme immunoassay that detects rubella‐specific immunoglobulin M immediately after disease onset. (30th January 2019) - Kurata, Takako; Uchino, Kiyoko; Hotta, Chiemi; Ogura, Atsushi; Miyoshi, Tatsuya; Ogawa, Tomoko; Kanbayashi, Daiki; Tanaka, Tomoyuki; Yumisashi, Takahiro; Komano, Jun
Abstract: A total of 300 patients with nucleic acid test‐confirmed rubella, mostly adults, were investigated to determine the clinical value of a rubella‐specific IgM test using an EIA kit. IgM titers increased after rash onset, the median IgM titer being significantly higher 3 days post‐onset than on previous days ( P  < 0.0001). Similarly, the IgM‐positive rate at 3 days post‐onset (61.5%) was significantly higher than on previous days ( P  < 0.0001). This IgM test against rubella at 3 days or more post‐disease onset provides the clinically relevant information.